Chápání trhu a tržního hospodářství v evangelické tradici - Jindřich Halama (Acta Universitatis Carolinae Theologica, 2016)
The contribution seeks to give a brief sketch of Protestant attitude to individual economic activities starting with the Reformation. It follows the development of socio-economic views in the Protestant churches in the time of Puritanism and later in the 19th century. It touches the famous thesis of Max Weber and its critiques and gives a picture of the birth of the so-called social market economy in Germany. The Protestant view accepts the basic account for market economy – the powerful human motive of self-interest that makes the market economy efficient. At the same time, the Protestant understanding of sin sees taming excessive manifestations of self-interest as inevitable. This brings a need for a continuous critique of the market economy and for efforts to balance its inclination to selfishness through effective mechanisms of social solidarity.